Alternatives to low birthweight as a population-level indicator of infant and child health - Daneeta Hennessy; Siranda Torvaldsen; Jason P Bentley; Jennifer R Bowen; Helen A Moore; Christine L Roberts (Sax Institute, 2022)
Background: Low birthweight (<2500 g) is often used as a population-level indicator of maternal-child health, as it is easy to measure and correlates with poorer infant health outcomes. However, it conflates preterm birth and intrauterine growth restriction, which have different causal pathways and require different approaches to prevention. Small for gestational age (SGA) (a proxy for growth restriction) and preterm birth may be more informative measures. We evaluated low birthweight as a population-level indicator. Methods: We conducted a population-based cohort study of singleton live births in New South Wales (NSW), Australia, using linked data from 1994-2006 birth, hospital, death and educational records, with follow-up until 2014. Outcomes of babies born of low birthweight, preterm and SGA were compared with well-grown term infants (i.e. not low birthweight or SGA). Overlap between groups and temporal trends were also examined. Results: Of 1 093 765 singleton live births, 47 946 (4.4%) infants were low birthweight and had poorer outcomes than well-grown term infants (2.7% vs. 0.1% infant mortality; 13% vs. 6% below national minimum numeracy standard). SGA and preterm infants also had poorer outcomes (0.5%, 2.3% infant mortality respectively; 10%, 11% below numeracy standard) but 80% of SGA and 47% of preterm infants were not low birthweight. For all outcomes, low birthweight identified a smaller proportion of infants with poor outcomes than preterm birth and than either SGA or low birthweight at term. The proportion of low-birthweight births remained constant over time, while the proportion of births that were preterm increased and proportion of SGA decreased. Conclusions: Low birthweight, SGA and preterm infants are all at higher risk of poorer outcomes but low birthweight inadequately captures, and masks trends in, both preterm births and births that are SGA. Reporting preterm births and an indicator of growth restriction at term will identify vulnerable groups better than using the measure of low birthweight.